Land Reform in Mozambique - Van den Brink, Rogier J. E. (World Bank, Washington, DC, 2014)
This brief includes the following headings: rationale, objectives, and basic features of the 1997 land law; acquiring land-use rights; obstacles to transferring urban land-use rights; promote the productive use of Direito de Uso e Aproveitamento dos Terras, or DUATs; and enforce the land tax.